FINANCIAL INCLUSION AND THE INFORMAL SECTOR DURING AND POST-COVID 19 ERAS: STATUS, CHALLENGES AND WAY FORWARD - Takupiwa NYANGA; Munyaradzi CHIKOVE; Thinkwell NYANGA (Business Excellence and Management)
COVID 19 is one of the major disasters that significantly disrupted the socio-economic statuses of various businesses and nations. The purpose of the study was to explore the extent to which COVID 19 affected financial inclusion in Zimbabwe. The qualitative research methodology and purposive sampling technique were adopted in carrying out the study. Data was collected using in-depth interviews and focus group discussions from 35 participants. Data was analysed using the thematic data analysis approach. The study found out that covid-19 barred people in rural areas from accessing financial services, which consequently propelled poverty in rural areas. Financial inclusion, is a key driver to poverty reduction; while financial exclusion significantly propels poverty in societies. The study also established that digitalizing financial services is one of the strategies which can be utilized to promote financial inclusion in the post- covid19 era. Financial institutions should digitalise financial services, so that those in rural areas do not incur transport and logistical costs to access financial services. It was recommended that policies that encourage the delivery of formal financial services to the informal business sector in rural areas should be developed. Governments should consider granting subsidy to providers of financial services in rural areas so that they can offer basic financial services at low cost to the excluded population. Thus, the government and financial institutions ought to commit themselves to the delivery of accessible, affordable, appropriate and cost-effective financial services in rural areas.